2018
DOI: 10.3389/fpls.2018.00724
|View full text |Cite
|
Sign up to set email alerts
|

Red Clover (Trifolium pratense) and Zigzag Clover (T. medium) – A Picture of Genomic Similarities and Differences

Abstract: The genus clover (Trifolium sp.) is one of the most economically important genera in the Fabaceae family. More than 10 species are grown as manure plants or forage legumes. Red clover’s (T. pratense) genome size is one of the smallest in the Trifolium genus, while many clovers with potential breeding value have much larger genomes. Zigzag clover (T. medium) is closely related to the sequenced red clover; however, its genome is approximately 7.5x larger. Currently, almost nothing is known about the architecture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 74 publications
2
30
1
Order By: Relevance
“…Our finding that two SNPs associated with seed size (length and width) and seed color are both localized in TE genes could be explained by the fact that other species from the Trifolieae tribe, in contrast to other legumes, have genomes that are rich in TEs. For example, Trifolium pretense and Trifolium medium genomes were reported to have more than 30 and 40%, respectively, of retrotransposable elements in their genome [ 24 , 52 ], and that our data show a similar trend for the fenugreek genome. Accordingly, this suggests an important role for TEs in shaping the fenugreek genome and thus in controlling important phenotypic and economic traits in addition to the ones studied here.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our finding that two SNPs associated with seed size (length and width) and seed color are both localized in TE genes could be explained by the fact that other species from the Trifolieae tribe, in contrast to other legumes, have genomes that are rich in TEs. For example, Trifolium pretense and Trifolium medium genomes were reported to have more than 30 and 40%, respectively, of retrotransposable elements in their genome [ 24 , 52 ], and that our data show a similar trend for the fenugreek genome. Accordingly, this suggests an important role for TEs in shaping the fenugreek genome and thus in controlling important phenotypic and economic traits in addition to the ones studied here.…”
Section: Discussionsupporting
confidence: 75%
“…This is similar to previous studies that reported synteny between M. truncatula and legumes such as white clover [ 23 ], red clover [ 56 ], birdsfoot trefoil [ 57 , 58 ], common bean [ 58 ], chickpea and lentil [ 59 ], and faba bean [ 60 ]. Synteny was also reported between members of the Trifolieae tribe such as Red clover and zigzag clover [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2015 ) but are comparably less abundant in the related legume taxa ( Macas et al. 2007 ; Dluhošová et al. 2018 ), potentially resulting in smaller numbers of Ogre-derived satellite repeats.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known disadvantages of red clover include poor persistence under several land use 31 scenarios, like grazing or cutting [1][2][3]. T. pratense is a member of the Fabaceae (or legumes), which 32 are, due to their economic value, among the most examined families in the plant kingdom with 33 genome sequences available for species like Medicago truncatula (barrel clover) [4], Lotus japonicus 34 (birdsfoot trefoil) [5], Glycine max (soy) [6], Phaseolus vulgaris (common bean) [7], Cicer arietinum 35 (chickpea) [8], Vigna unguiculata (cowpea) [9],Trifolium subterraneum (subterranean clover) [10] 36 Trifolium medium (zigzag clover) [11], and T. pratense (red clover) [12,13].…”
Section: Introduction 27mentioning
confidence: 99%